Adiposity, psychomotor and behaviour outcomes of children born after maternal bariatric surgery. Issue 5 (17th November 2020) - Van De Maele, Karolien; Bogaerts, Annick; De Schepper, Jean; Provyn, Steven; Ceulemans, Dries; Guelinckx, Isabelle; Gies, Inge; Devlieger, Roland
Summary: Background: Bariatric surgery before pregnancy can result in improved maternal fertility. However, long‐term data on the consequences at childhood age are currently lacking. Methods: EFFECTOR is a prospective cohort study of children (aged 4 to 11 years) born to mothers who underwent bariatric surgery (BS) before pregnancy (n = 36), controls with overweight/obesity (OW/OB) matched on pre‐pregnancy BMI (n = 36) and normal weight controls (NL) (n = 35). We performed prospective collection of anthropometric data, data on psychomotor development, school functioning and behaviour (Strengths and Difficulties Questionnaire (SDQ), Child Behaviour Checklist (CBCL)). Results: The children born after bariatric surgery (BS) presented with the highest body‐weight SDS (0.70 vs 0.14 in OW/OB and −0.09 in NL; P = .006) and BMI SDS (0.47 vs −0.02 in OW/OB and −0.42 in NL; P = .01). A higher excess in body fat percentage and waist circumference SDS were found in the BS group (5.7 vs 1.4 in OW/OB and −0.1 in NL; P < .001 and 0.61 vs 0.16 in OW/OB and −0.15 in NL; P = .04). The SDQ questionnaires revealed a higher amount of overall problems in the BS offspring (11.1 vs 7.5 in OW/OB and 8.1 in NL; P = .03), with a higher externalizing score at the CBCL (52.0 vs 44.2 in OW/OB and 47.0 in NL; P = .03). Conclusion: Maternal bariatric surgery does not appear to protect the offspring for childhood overweight and obesity. Parents reported more behaviour problems in these children, especially externally of nature.